1974
DOI: 10.1210/endo-95-5-1439
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Insulin: Radioimmunological Characterization and Enhanced Activity in Rat Fat Cells and Liver Plasma Membranes

Abstract: Insulin was extracted from chicken pancreases and purified; its chemical, immunological and biological properties were investigated. The chicken insulin preparation appeared homogeneous on polyacrylamide gel electrophoresis and its amiho acid composition was similar to that previously described by others. Among 21 guinea pig antihuman, anti-bovine and anti-porcine insulin sera, only one anti-porcine and two anti-human insulin sera cross-reacted with chicken insulin to a large extent. With one of them, chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…A large cross-reaction has been observed between chicken insulin and the guinea pig anti-porcine sera (Simon et al, 1974 this study is referred to as immunoreactive insulin. The sensitivity of the assay was 1 μIU ml −1 , and all of the samples were included in the same assay to avoid inter-assay variability.…”
Section: Measurement Of Plasma Insulin Levelsmentioning
confidence: 92%
“…A large cross-reaction has been observed between chicken insulin and the guinea pig anti-porcine sera (Simon et al, 1974 this study is referred to as immunoreactive insulin. The sensitivity of the assay was 1 μIU ml −1 , and all of the samples were included in the same assay to avoid inter-assay variability.…”
Section: Measurement Of Plasma Insulin Levelsmentioning
confidence: 92%
“…Plasma insulin levels were determined by radioimmunoassay as previously described by Simon et al (1974). The lowest limit of sensitivity was 2 m U/ml, and interassay variation was less than 10%.…”
Section: Histological Analysismentioning
confidence: 99%
“…It was generally suggested that the enhanced activities of [A8His]Ins [11] , chicken and turkey insulins were ascribed to the His at A8 [12][13][14] , which should account for the higher affinity for insulin receptor. Our results showed that the presence of His at A8 apparently did not enhance the receptor binding.…”
Section: Discussionmentioning
confidence: 99%